Analisis Beban Kerja Mental Karyawan Departemen Engineering Pada PT. Z Menggunakan Metode NASA-TLX - Lydia Maulani; Risma Fitriani; Wahyudin, Wahyudin (Fakultas Teknik Universitas Tulang Bawang, 2024)
Human resources (HR) work activities are very important for business processes, so human resource factors must be taken into account and paid attention to. This research was conducted at the Engineering Department of PT. Z is responsible for product design and product development. This research aims to measure the workload of Engineering Department employees at PT. Z in order to increase employee productivity. This research uses the National Aeronautics and Space Administration Workload Index (NASA-TLX) method. This method is used to analyze the mental workload felt by Engineering Department employees when carrying out work activities and is expected to improve an existing system to increase work comfort and productivity. Based on the final NASA TLX score for the Engineering Department of PT Z, five employees have a very high level of mental workload, two employees have a high level of mental workload, two employees have a medium level of mental workload, and one employee has a light level of mental workload. Then for the mental workload of PT employees. Z based on the NASA-TLX method obtained an average WWL value of 72.9, which means it is included in the mental load classification, therefore there is a need for work improvement. Keywords: Ergonomics, Mental Load, NASA-TLX, Workload